About the benefits of carbon dioxide capture technology in Polish realities - Woszczyk, Paweł; Kaczanowski, Michał (Instal, 2022)
The purpose of this article is to present the benefits of using carbon dioxide capture technology in the National Power System. The article presents not only aspects related to the current geopolitical situation, but also technical issues. In addition, the text presents the current trends related to CCS and what the prospects for this technology look like in the near future.
Keywords: Poland; power industry; conventional power industry; CCS; carbon dioxide capture; clean coal technologies